THE EFFECTIVENESS OF THE DEVELOPMENT INSTITUTIONS. CHANGE OF PARADIGMS OF DEVELOPMENT INSTITUTIONS IN THE MEDIUM-RANGE PERSPECTIVE - A. N. Petrov (Èkonomika Nauki, 2018)
The article presents an analysis of issues around the operations of state development institutions in the scientific-technical and innovation fields. There are suggested hypothesis and models, by which there are offered measures for improving the systems of development institutions. The basis for accepting an investment solution inside any developmental institution should be a confirmed commitment of the end consumer of the technology, product, innovation enterprise. It is necessary to accept the system of regulatory measures to stimulate the coordination between developmental institutions, provision of a transparent support for projects within the whole chain of innovative development. The solution for issues with the deficiency of investment resources at the stage of creation and expansion of the prototype (Stage B+), specialised expertise, lays in new field foundations, created with the state capital.